Development of a real-time hot-spot prevention using an emulator of partially shaded PV systems. (November 2018) - Bressan, M.; Gutierrez, A.; Garcia Gutierrez, L.; Alonso, C.
Abstract: This work presents an emulation in real-time of the shaded PV systems with a hot-spot prevention. The PV model takes into account the photo-induced current contributions from unshaded and shaded sides thanks to parameters such as the shadow transmittance and the percentage area of the shadows. The use of shadow fault detection in real time is employed avoiding all form of hot-spot formation and PV cells power dissipation. The calculation uses a simple derivative equation able to give the area of detection in function of the PV module voltage. The implementation of the emulator in FPGA takes advantages as a result of their features of adaptability and parallel processing suitable for emulation of complex shading visible on PV systems. The emulation of the proposed PV model and the hot-spot prevention are validated through two experimental tests on PV modules. Highlights: An accurate emulator in real-time of the shaded PV systems is developed with a hot-spot prevention. The PV model takes into account parameters such as the shadow transmittance and the percentage area of the shadows. This works presents accuracy results implemented in FPGA. The hot prevention algorithms are explained through flowcharts.